American literature's aesthetic dimensions - Weinstein, Cindy; Looby, Christopher (Columbia University Press, 2012)
In these diverse essays, leading critics recast the place of aesthetics in the production and consumption of literature. Rethinking the category of aesthetics in light of recent developments in literary theory and social criticism, contributors showcase the interpretive possibilities available to those who bring politics, culture, ideology, and conceptions of identity into their critiques. Deploying a distinctive range of methodologies, essays combine close readings of individual works and authors with more theoretical discussions of aesthetic theory and its relation to American li.